Impacts of COVID-19 pandemic on early life gut microbiome - Lin Zhang; Wenye Xu; Henry Y. H. Meng; Jessica Y. L. Ching; Yingzhi Liu; Shilan Wang; Shuai Yan; Ling Lin; Pui K. Cheong; Ka L. Ip; Ye Peng; Jie Zhu; et al. (Gut Microbes)
Increased hygiene and sanitation are theorized to predispose to developing atopic diseases, a process potentially mediated by the gut microbiome. We hypothesized that the gut microbiome maturation has been altered by COVID-19 lockdown measures during the first year of life, a critical period when environmental exposure shapes human microbiome development. The two large pre- and during-COVID-19 mother-baby pairs cohorts in the Greater Bay Area of China provided the unique opportunity to assess the effect of increased hygiene standards on early gut microbiome maturation. Our results showed that the gut microbiome diversity, composition, and developmental trajectory were significantly altered between pre- and during-COVID-19 cohorts. Functionally, there was decreased richness in both antimicrobial peptide resistance genes and antibiotic resistance genes in the during-COVID cohort. Specially, Staphylococcus epidermidis carried a lower copy number of fluoroquinolone and beta-lactam antibiotics resistance genes while Klebsiella pneumoniae possessed a higher copy number of fluoroquinolone antibiotic resistance genes in gut microbiota of infants born during the COVID-19 pandemic. Our study underscores the importance of considering the microbiome when evaluating hygiene measures and the need for future research to ascertain the role of the gut microbiome in disease development.